NILAM SARI LAWIRA THE WOMEN’S DAKWAH IN CENTRAL SULAWESI - Harun, Makmur; Syamsuri, Syamsuri; Minannur, Minannur (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
Nilam Sari Lawira actively supports dakwah activities among women in Central Sulawesi. Starting from teenage girls, housewives, to working professionals. The forum for religious education (majelis taklim) has become identical for women to study Islam. The female clerics took part in learning activities so as to create messages and contents of preaching strong gender access.The theory of sanad hadis that places female narrators conveying the hadiths of the Prophet Muhammad SAW has succeeded in demonstrating the power of women's dakwah that continues until now. The results of the study show that Nilam Sari Lawira has the power of science in providing adequate infrastructure and financial facilities for the success of women's preaching in Central Sulawesi.